Design and Build a Public Complaint Feature Via WhatsApp on the Adu.in Website with the Scrum Method : Case Study: West Java DPRD - Hazdia, Aprilita Firsty; Utama, Nur Ichsan; Suakanto, Sinung (Jurnal Indonesia Sosial Sains, 2024)
The importance of the role of members of the Regional People's Representative Council (DPRD) as representatives of the community requires active involvement in absorbing, accommodating, collecting, and following up on community aspirations and complaints. However, the complaint process often faces obstacles that result in delays in resolving problems, ranging from the complexity of the complaint flow to the difficulty of finding an effective complaint platform. To overcome these challenges, an innovative step was taken, which was to create a website that provides a complaint feature via WhatsApp. The main objective of this initiative is to provide easier access to the community to participate in raising their complaints and complaints. With the WhatsApp complaint platform, it is hoped that the community can quickly and efficiently report problems and provide feedback to the local government. The WhatsApp complaint feature is integrated to minimize technical barriers and facilitate use by the wider community. Through this website, people can easily file complaints, send messages, and provide documentation related to the problems faced. With the implementation of this platform, it is expected that problem-solving can be done more efficiently and responsively. Thus, creating a public complaint website with a complaint feature via WhatsApp is not only a practical solution in dealing with the obstacles of the complaint process but also a significant step in encouraging active public participation in building a transparent and accountable government.